Pertumbuhan Trichoderma harzianum pada Medium yang Mengandung Xilan - Priyo Wahyudi; Untung Suwahyono; Sri Mulyati (Fakultas Farmasi Universitas Pancasila, 2004)
Xylan is one of the most important components of hemicelluloses, which could be enzimatically hydrolized by xylanolytic enzymes. One of the xylanase producing fungi is Trichoderma harzianum, which growth in a medium requires sufficient nutrient, such as Carbon, Nitrogen, microelements and vitamins. Xylan as a polysaccharide could be used as Carbon source in a growth medium of T. harzianum. The purpose of this experiment is to assess the growth ability of T. harzianum in a medium with xylan as a sole Carbon source. Three media are tested in this experiment, i.e. Medium I, Medium II, and Medium III. The result shows that the best growth of T. harzianum is obtained in Medium III, followed by Medium II and then Medium I. The best medium pH is neutral (+7) to mild acidic (6.2).